Kewenangan Notaris Di Bidang Cyber Notary Berdasarkan Implementasi Hukum Kenotariatan Demi Terwujudnya Kepastian Hukum - Atmasari, Ni Nyoman Ayu Anggarina; Dahana, Cokorda Dalem (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 9 No 03 (2024), 2024)
The purpose of this study is to determine and analyze the making of notarial deeds for electronic transactions and the analysis of notary authority in the field of cyber notary in Indonesia. This legal research is a normative legal research with a conceptual and statutory approach. The legal materials of this study are based on primary, secondary and tertiary legal materials. Based on the results of the study, the following conclusions can be formulated: (1) Article 17 letter a in conjunction with Article 18 UUJN explains that the making of electronic deeds by notaries is not bound by the notary's area of ??office; and (2) Notaries obtain their authority by means of attribution, so that in the process of making authentic deeds online it can be done with sophisticated usage facilities such as video conference facilities that allow the deed to be read by the notary through the media to be heard and witnessed by the parties online.